Inhibition of Mineralisation of Urinary Stone Forming Minerals by Naturally Occurring Acids - Rao, T.V.R.K.; Bano, Sofia (Asian Journal of Chemistry, 2010)
Naturally occurring acids. viz., lactic, malic, tartaric, citric or succinic acids have been studied as inhibitors in the mineralisation of winary stone forming minerals, viz., calcium phosphate, oxalate or carbonate. Inhibition efficiency has been studied in different experimental models. Utility of these acids in urolithiasis inhibition has been discussed.